Analisis Faktor-faktor yang Mempengaruhi Loyalitas Merek pada Konsumen California Fried Chicken (CFC) di Kota Langsa - Ririn Tamaya; Refi, Teuku Muana (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
This research was conducted with the aim of knowing the factors that influence Brand Loyalty to consumers of California Fried Chicken or known as CFC in Langsa City. The sample in this study were consumers totaling 88 respondents. Primary data from the questionnaire results, then the data is tabulated with a Likert scale, analyzed with multiple linear regression equipment, hypothesis testing with t test, F test, correlation coefficient testing, and determination testing. Based on the research results obtained Y = 7.089 + 0.251 (Product Quality) + 0.283 (Service Quality) + 0.202 (Promotion) + 0.233 (Price). The constant coefficient of 7.089 is the value of the dependent variable (Brand Loyalty) if the value of the independent variable is constant (fixed) or has a value of zero. This shows that the dependent variable (Brand Loyalty) is influenced by the independent variable (Product Quality, Service Quality, Promotion, Price) of 7,089. The correlation coefficient value which is symbolized by R is 0.690 which can be equated with the relationship of the independent variable which is classified as strong towards the dependent variable, while the value of the coefficient of determination (R2) is 0.476, indicating that the independent variable influences the dependent variable (Brand Loyalty) of 0.476 or if it is percentaged 47.6% and the remaining 52.4% is influenced by other variables not examined in this study. The results of hypothesis testing (t test and F test) obtained the significance level of the independent variable with Service Quality Factor (X1) 3.000 > 2.633 and 0.04 <0.05, Service Quality Factor (X2) 3.972 > 2.633 and 0.00 <0. 05, Promotion Factor (X3) 3.292 > 2.633 and 0.01 < 0.05, and Price Factor (X4) 4.023 > 2.633 and 0.00 < 0.05. This shows that the independent variable has a positive and significant effect on Brand Loyalty. Thus the hypothesis is accepted. Keywords: Brand Loyalty, Consumer, California Fried Chicken (CFC) in Langsa City